2016
DOI: 10.1534/genetics.112.145243
|View full text |Cite
|
Sign up to set email alerts
|

The Nuts and Bolts of Transcriptionally Silent Chromatin in Saccharomyces cerevisiae

Abstract: Transcriptional silencing in Saccharomyces cerevisiae occurs at several genomic sites including the silent mating-type loci, telomeres, and the ribosomal DNA (rDNA) tandem array. Epigenetic silencing at each of these domains is characterized by the absence of nearly all histone modifications, including most prominently the lack of histone H4 lysine 16 acetylation. In all cases, silencing requires Sir2, a highly-conserved NAD + -dependent histone deacetylase. At locations other than the rDNA, silencing also req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
168
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(171 citation statements)
references
References 425 publications
(604 reference statements)
3
168
0
Order By: Relevance
“…Strikingly, we found that the disruption of SIR2 did not significantly increase global levels of H4K16ac in either NDT80 or ndt80 cells (Figures 5 and 6C), consistent with the notion that Sir2 is not the main genome-wide H4K16ac deacetylase and its action may be specifically restricted to precise heterochromatic domains 5354. On the other hand, SAS2 deletion clearly, but not completely, reduced H4K16ac (Figures 5 and 6C), suggesting that Sas2 is the main, but not the only, H4K16 acetyltransferase acting in the meiotic cell cycle.…”
Section: Resultssupporting
confidence: 85%
“…Strikingly, we found that the disruption of SIR2 did not significantly increase global levels of H4K16ac in either NDT80 or ndt80 cells (Figures 5 and 6C), consistent with the notion that Sir2 is not the main genome-wide H4K16ac deacetylase and its action may be specifically restricted to precise heterochromatic domains 5354. On the other hand, SAS2 deletion clearly, but not completely, reduced H4K16ac (Figures 5 and 6C), suggesting that Sas2 is the main, but not the only, H4K16 acetyltransferase acting in the meiotic cell cycle.…”
Section: Resultssupporting
confidence: 85%
“…Previous studies showed that the aging phenotype with small round daughters could be related to an age-dependent mitochondrial dysfunction (9,12), but the molecular mechanisms underlying the other aging type characterized by elongated daughters remain largely unclear. Our results revealed that the sustained rDNA silencing loss, which can lead to genome instability (18), is specifically associated with the aging phenotype featured by elongated daughters. In support of this, young mother cells can also sporadically produce a few elongated daughters, the occurrence of which correlates with the transient silencing loss during the early phases of their life spans (Fig.…”
Section: Significancementioning
confidence: 69%
“…A major contributor to the maintenance of genome stability is chromatin silencing, which causes a locally inaccessible heterochromatin structure that represses transcription, recombination, and DNA damage. The heterochromatic regions in yeast include the silent mating-type (HM) loci, rDNA, and subtelomeric regions (18). Among them, the rDNA region on chromosome XII consists of 100∼200 tandem repeats and is a particularly fragile genomic site, the stability of which closely connects to the RLS (19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations